Multidetector computed tomography in evaluation of buccal mucosa cancer - Nikhilendra Reddy AVS; Deepti Naik; Anil Kumar Sakalecha; Rajeswari G; Yashas Ullas L; Revanth RB; Suryakanth Anne (Asian Journal of Medical Sciences, 2023)
Background: Squamous cell carcinoma is the most prevalent kind of tumor of the buccal mucosa. For the purpose of planning surgery and radiotherapy for tumors of the tongue, floor of the mouth, and oropharyx, imaging to locate the size and extent of the original tumor is essential. Therefore, it is beneficial to determine the radiation field, to ensure adequate tumor margin excision, and overall to improve the patient’s prognosis. Aims and Objectives: The aim of the study was to evaluate the role of computed tomography (CT) scan in diagnosis of buccal mucosal malignancies and its characteristics. Materials and Methods: Total 50 patients suspecting buccal mucosa cancer were referred to Radiology Department. They were subjected for CT scan examination on 16 slice CT scanner. CT scan evaluation was made for size and extent of primary mass lesion. The staging of disease was performed with TNM classification. Results: In our study, out of 50 patients, the fourth decade (30%) and fifth decade (26%) saw the highest incidence of buccal mucosa cancer. The majority of the patients were suffering from severe disease; 44% had T4 stage and 58% had Stage IV. Conclusion: CT plays a very important role in staging of buccal mucosa malignancy and effectively detects bone erosion (98% sensitive) and invasion to infratemporal fossa. However, during the early stages of cancer, a CT scan might not be very helpful.